Local community resistance in Lombok against tourism development policy - Winengan Winengan (Masyarakat, Kebudayaan dan Politik, 2019)
Since the enactment of decentralization policies regarding tourism management of regions, developing tourism areas have grown to become a central issue for the local government, who have tackled it through a land acquisition policy against local communities. This study intends to examine the formulation and process of government land acquisition policies for the development of tourism areas in Lombok, whose decisions are met with opposition from the local community. This research uses qualitative and snowball techniques to determine informants. Data collection is carried out in the form of interviews, documentation, and observation. The results of this study reveal that community resistance to tourism development policies is a clear example of the lack of the power the local communities have in the policy formulation process (which stipulates land acquisition as a formulation of its policies). In its formulation, regional tourism policies have undergone a systematic process. However, if the policy option does not reflect the results of a comprehensive study - which only considers economic and business benefits and is not participatory in providing space for local communities to articulate their interests - it will lack legitimization and will be met with resistance from the local community.